Membangun Sinergitas Berfikir Positif Melalui Hipnoterapi Pada Majelis Taklim An Nur Terhadap Dampak Covid 19 - Rachayu, Imma; Lesmana , Sastria Agustian; Juarsa , M.Sidik; Juwita; Luthfia , Izza (Jurnal Kewirausahaan dan Bisnis, 2020)
The objectives of this activity are: 1). Providing knowledge about cultivating the ability to think positively despite the many pressures faced during the current Covid-19 pandemic, 2) Providing training and motivation to the women of the Taklim An Nur assembly in the city of Bengkulu through hypnotherapy. Based on the results and evaluation of the activities, it can be concluded that the activities that have been carried out can build positive thinking synergy through the subconscious that oneself has by implementing self-hypnosis so that they are able to deal with all the problems that arise in the current era of the Covid 19 pandemic, especially the women of the assembly. Taklim An Nur, Rawa Makmur Village, Bengkulu City.